2015
DOI: 10.1038/ncomms7603
|View full text |Cite
|
Sign up to set email alerts
|

Local cooling and warming effects of forests based on satellite observations

Abstract: The biophysical effects of forests on climate have been extensively studied with climate models. However, models cannot accurately reproduce local climate effects due to their coarse spatial resolution and uncertainties, and field observations are valuable but often insufficient due to their limited coverage. Here we present new evidence acquired from global satellite data to analyse the biophysical effects of forests on local climate. Results show that tropical forests have a strong cooling effect throughout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

51
534
3
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 477 publications
(649 citation statements)
references
References 53 publications
51
534
3
1
Order By: Relevance
“…The ETs were significant, highlighting that despite their higher albedo, all land cover types had higher LSTs than forests related to lower ET rates than forests. In contrast, forests that absorb more solar radiation because of the lower albedo have lower LST because of the higher ET they exhibit, hereby identifying evaporative cooling as the main determinant of regulating the surface temperature of all vegetation cover types (Li et al, 2015). Both observational and modeling studies carried out in other geographic regions and with other trajectories support our observations.…”
Section: Drivers Of Local Differences Between Different Land Cover Typessupporting
confidence: 77%
See 3 more Smart Citations
“…The ETs were significant, highlighting that despite their higher albedo, all land cover types had higher LSTs than forests related to lower ET rates than forests. In contrast, forests that absorb more solar radiation because of the lower albedo have lower LST because of the higher ET they exhibit, hereby identifying evaporative cooling as the main determinant of regulating the surface temperature of all vegetation cover types (Li et al, 2015). Both observational and modeling studies carried out in other geographic regions and with other trajectories support our observations.…”
Section: Drivers Of Local Differences Between Different Land Cover Typessupporting
confidence: 77%
“…Similar effects were also observed for other South American biomes (Salazar et al, 2016). In a global analysis, Li et al (2015) showed that the cooling of forests is moderate at midlatitudes but northern boreal forests are warmer, an indication that the effect of land cover change on LST varies with the location of the land cover change (Longobardi et al, 2016). Similar studies on the Indonesian islands are lacking but surface temperature increases are expected as an effect of oil palm and cash crop land expansion in the recent decades.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…There are two kinds of observations, that are widely used to explore the effects of forests on temperature: satellite and in-situ data [7,14,[17][18][19][20]. Some studies used satellite observations found that afforestation in China cooled daytime temperatures and warmed the nocturnal temperatures [18,20].…”
Section: Introductionmentioning
confidence: 99%